Professional insecurities: a guide to understanding and career management - Brunner, Ronald D.; Willard, Andrew R. (2003)
Professional insecurities include the expectation that one's job or career, and all that depends upon it, are at risk through denial of tenure, dismissal from an official position, or other sanctions for non-compliance with established practices. The expanding subdivision of work in modern society exacerbates professional insecurities by precipitating conflicts of conscience and by proliferating practices that are often ambiguous and incompatible, but nevertheless must be taken seriously because they are expected to be enforced with severe sanctions. This article suggests how the problem of professional insecurities might be understood and managed by aspiring policy scientists especially, and by others as well. There are no universal or final solutions to the problem, but there are better working solutions for particular persons and situations if we are intelligent enough to find them through applications of central theory. - Reproduced.
Keywords: Career development